REVIEW: PHYSICAL CHARACTERISTICS, ANTIOXIDANT, ANTIBACTERIAL AND WOUND HEALING EFFECTS OF BASIL LEAVES IN SEVERAL TYPES OF PHARMACEUTICAL BASES - Rodhia Ulfa; Wildan Khairi Muhtadi; Nesa Agistia; Haiyul Fadhli (Medical Sains : Jurnal Ilmiah Kefarmasian, 2023)
Topical preparations are dosage forms applied to the skin for local therapy. These topical preparations contain several types of bases that are used for drug formulations. This review aimed to determine the type of base that is effective and widely used in basil leaf preparations that function as antioxidants, antibacterial agents, and in wound healing. The research method is comparative, namely, reviewing research articles on formulations of basil leaf products with various concentrations of base types, hydrogels, emulgels, lotions, hydrocarbons, water solubility, absorption, water washing, M/A-type creams, and pastes. The recommended formulation is a gel base type that has physical characteristics, non-irritating properties, antioxidant activity, antibacterial activity, and wound healing. This review contained articles published in the last 10 years. Â Keywords: basil leaves, base type, physical characteristics, basil leaves, pharmacological activity